Brain metastases in patients with breast cancer - Litwiniuk, Maria; Łojko, Anna; Markowska, Janina (Contemporary Oncology/Współczesna Onkologia, 2004)
Breast cancer is the second, after lung cancer, most common cause of brain metastases. Brain metastases are always indicative of very poor prognosis. The average survival time of patients without treatment is one month. While no optimal treatment of brain metastases has been yet established, the introduction of new pharmaceuticals to the therapy of cancer has resulted in a longer survival time of patients with a metastatic disease. Consequently, the number of patients with brain metastases will be growing. Studies suggest that patients with a single brain metastasis who have undergone a surgical resection followed by radiotherapy have better survival results than patients treated with radiotherapy alone. However, surgery is limited to a selected group of patients because it can only be performed on patients with a solitary brain metastasis and no evidence of visceral metastases. The aim of our study was a retrospective analysis of breast cancer patients with brain metastasis treated in the Clinic of Oncology in Poznań between 1990 and 2002. A group of 29 patients was identified as eligible for the study. Five patients underwent surgery and ± postoperative radio/chemotherapy. Those patients have median survival of 12 months. In the group of patients on whom the surgery was not performed, chemotherapy combined with radiotherapy improved the survival results (median survival 7.7 months against 1.2 months for those treated with radiotherapy alone). From the above we may conclude that in patients with breast cancer and brain metastasis, the best results and the longest survival time can be achieved when the surgical procedure is followed by radio/chemotherapy. Consequently such combined treatment should be more often considered and recommended.